The Role of Knowledge Capital in Total Factor Productivity Changes: The Case of Agriculture in EU Countries - Tomasz Kijek; Anna Nowak; Katarzyna Domanśka (German Journal of Agricultural Economics (GJAE), 2016)
The present study concerns the impact of knowledge capital on total factor productivity (TFP) changes in 27 European Union (EU) countries. The TFP analysis covered the years 2009-2013. The study conducted was based on a Malmquist productivity index. The knowledge capital was approximated through investments in research and development in the years 2000 and 2008. Furthermore, the study included
Keywords: 330